2013
DOI: 10.1155/2013/909328
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Transplantation Alters the Disease Progression in Becker’s Muscular Dystrophy

Abstract: Becker's Muscular Dystrophy (BMD) is a dystrophinopathy manifested as progressive muscle degeneration. Autologous Bone Marrow Mononuclear Cells (BMMNCs) have shown some myogenic potential. The paracrine effects of the BMMNCs reduce the inflammation and are thought to reduce muscle degeneration. We treated a 39 year old dental surgeon suffering from BMD. Muscle strength was reduced when measured using modified Medical Research Council's Manual Muscle Testing (mMRC-MMT). Static sitting balance was poor. He was w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…A recent case study showed increase in the muscle fibers of peronei, gastrosoleus and long, medial and lateral head of triceps with decreased fatty infiltration as observed on the MRI-MSK post 6 months of cellular transplantation in BMD which is almost similar to our study. 20 …”
Section: Discussionmentioning
confidence: 99%
“…A recent case study showed increase in the muscle fibers of peronei, gastrosoleus and long, medial and lateral head of triceps with decreased fatty infiltration as observed on the MRI-MSK post 6 months of cellular transplantation in BMD which is almost similar to our study. 20 …”
Section: Discussionmentioning
confidence: 99%
“…Studies have also demonstrated the efficacy of autologous bone-marrow derived MNCs in improving the quality of life of patients with muscular dystrophy. 6,7,22 The main aim of cell therapy in patients with muscular dystrophy is to directly aim at regeneration of wasted adult muscle fibers through systemic and targeted injection of cells. These cells work toward blocking the deleterious process of muscle loss, thereby restoring, at least partially, the normal muscle function.…”
Section: Discussionmentioning
confidence: 99%
“…5 Thus, autologous BMMNCs have been postulated to promote muscle regeneration, promote repopulation of muscle by host cells, and improve muscle function and pathology, thus translating into enhanced functional outcomes. [6][7][8] Though the genetic defect in patients with LGMD cannot be repaired, the resultant muscle damage, which is progressive with time, can be repaired and the progression may be arrested or slowed down with the cell therapy, thus altering the course of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…He has taken records of the treatment results of many of his patients, using standardized outcome measures and, where possible, long-term follow-up procedures. None of these results have been published in top international journals, but Sharma has used open-access, pay-to-publish medical journals to publish individual case reports ( Sharma et al, 2013a , 2013b , 2013e , 2014a , 2014b ), and nonrandomized open-label clinical studies ( Sharma et al, 2012 , 2013c , 2013d ). Sharma has also published an e-book, a collection of 100 individual case reports of patients with muscular dystrophy ( Sharma et al, 2011 ).…”
Section: Case Study I: Ianrmentioning
confidence: 99%